Analysis of manganese nodules from the East Pacific - Piper, David Z (Supplement to: Piper, DZ (1973): Origin of metalliferous sediments from the East Pacific Rise. Earth and Planetary Science Letters, 19(1), 75-82, https://doi.org/10.1016/0012-821X(73)90179-9, 1973)
The distribution of several metals in East Pacific Rise sediments, when normalized to Al2O3, exhibit stronger maxima near the rise crest than when simply plotted on a carbonate-free basis. The similarity (1) between the distribution of metals in ridge sediments and previously measured mean heat flow values and (2) between the composition of crestal sediments and terrestrial ore bodies associated with greenstone belts, strongly supports a hydrothermal origin for rise crest sediments.